2007
DOI: 10.1089/acm.2007.7099
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Randomized Controlled Trial on the Effectiveness of Highly Concentrated Saline Spa Water Baths Followed by UVB Compared to UVB Only in Moderate to Severe Psoriasis

Abstract: The study indicates that HC-SSW-UVB are superior to routine UVB at the end of a 6-week treatment course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 24 publications
0
38
0
3
Order By: Relevance
“…The results of the second trial, involving 143 patients, indicated that BPT using low-concentration saline spa water baths followed by conventional UVB phototherapy was superior to conventional UVB monophototherapy at the end of a 6-week treatment course [8]. The same study group showed in another trial that psoriasis patients allocated to highly concentrated saline spa water baths plus UVB phototherapy for 6 weeks achieved a statistically significantly higher rate of PASI-50 than patients allocated to UVB only [9]. The concentration and mineral composition of the salt solution were thought to play a major role in BPT for psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the second trial, involving 143 patients, indicated that BPT using low-concentration saline spa water baths followed by conventional UVB phototherapy was superior to conventional UVB monophototherapy at the end of a 6-week treatment course [8]. The same study group showed in another trial that psoriasis patients allocated to highly concentrated saline spa water baths plus UVB phototherapy for 6 weeks achieved a statistically significantly higher rate of PASI-50 than patients allocated to UVB only [9]. The concentration and mineral composition of the salt solution were thought to play a major role in BPT for psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Für diese Modalität wurden Studien mit Behandlungsfrequenzen von zwei [181], drei [182][183][184][185][186], fünf [187,188] [191], zweimal [192][193][194], dreimal [147,184,195,196] oder 4 x/Wo [193,197] In mehreren kleinen [195,[199][200][201] sowie einer größeren nichtrandomisierten Studie [202] [197,212] treten jedoch mit ca. 5 % eher selten auf [197].…”
Section: Uv-b (Breitspektrum)unclassified
“…On the other hand, Health Resort Medicine, Balneology, Medical Hydrology and Climatology are relevant parts of the health systems in many countries within and outside Europe (Germany, Austria, Poland, Hungary, France, Japan, and others), and health insurances refund health resort treatments, at least partly. Additionally, it should be noted that a great deal of scientific work on the physiological mechanisms of these therapies (Gutenbrunner et al 1999a(Gutenbrunner et al , b, 2001aFink et al 2001;Shehata et al 2006;Bender et al 2007;Braga et al 2008;Vaile et al 2008) and their clinical outcomes (Gutenbrunner et al 1997(Gutenbrunner et al , 2001bGundermann et al 1998;Gutenbrunner and Gundermann 1998;Fioravanti et al 2000;Franke et al 2000;van Tubergen et al 2001;Costantino and Lampa 2005;Costantino et al 2006;Cutovic et al 2006;Gusi et al 2006;Balint et al 2007;Bellometti et al 2007;Brockow et al 2007a;Eversden et al 2007;Evcik et al 2007;Fransen et al 2007;Franke et al 2007a; Karagülle et al 2007a;Lund et al 2008;Odabasi et al 2008;Silva et al 2008;Tomas-Carus et al 2008) has been published within the last decades (for an overview see Gutenbrunner and Hildebrandt 1998;Bender et al 2005;Gutenbrunner 2006); in particular, the number of randomised prospective controlled studies has grown recently (Forestier 2000;StraussBlasche et al 2000a;…”
Section: Introductionmentioning
confidence: 99%